Hyperechoic Content of the Fetal Colon Is Not Always Cystinuria—Case Report - Knapke, Antje; Bourdat Michel, Guylhène; Marey, Isabelle; Le Tanno, Pauline (Frontiers in Pediatrics, 2022)
Cystinuria is a recessively inherited genetic disease causing recurrent kidney stones with risk of kidney failure. The discovery of hyperechoic colonic content on antenatal ultrasound is considered as a pathognomic sign of cystinuria. Herein, we present a clinical case with antenatal diagnosis of cystinuria on ultrasound finding, which eventually revealed a multisystem disease, characterized by the association of renal Fanconi syndrome, hyperinsulinemic hypoglycemia and hepatic dysfunction. Genetic investigations evidenced the recurrent heterozygous missense HNF4A p.(Arg76Trp) variant. Our case report shows that antenatal hyperechoic colonic content can hide a complex proximal renal tubulopathy, and questions the genetic counselling provided to families in the antenatal period.